The Role of Competitive Advantage in Mediating the Relationship Between Digital Transformation and MSME Performance in Bali - Ni Putu Yeni Yuliantari; Ni Made Wisni Arie Pramuki (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2022)
Advances in technology and digital-based information are expected to be put to good use by conventional business people. The pressure of the global COVID-19 pandemic that hit the world has an impact on the acceleration of digital transformation for business people, especially MSMEs. MSMEs as a sector of the national economy that has proven to be able to survive in a crisis are encouraged to accelerate the digital transformation process due to the social distancing policy imposed during the COVID-19 pandemic. This study aims to investigate the role of digital transformation on the performance of MSMEs through competitive advantage. This study uses quantitative methods and the data was collected using a questionnaire instrument. This survey was conducted in July-September in the midst of the covid-19 pandemic. The research location was carried out in MSMEs registered in 9 regencies/cities throughout Bali with a total of 326,000 with a total sample of 400 MSME managers. The results of this study found that all proposed hypotheses were acceptable and competitive advantage served as a partial mediation of the relationship between digital transformation and MSME performance.